REVOLUTIONS FROM NORTHERN AFRICA: A GRAND QUESTION FOR MANKIND? - CIPRIAN NIMARĂ; GRIGORE BUIA (Annals of the University of Petrosani: Economics)
The spring of the indignations against the presidents of the North African states and in the Middle East has aroused worldwide interest, not only in terms of their political effects in those states, but rather in terms of how these events have been suppressed by authoritarian regimes and the effects on the global economy and geopolitics.